Design motocyklu na elektrický pohon - Vítek, Jan (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2022)
Ve světě stále sílí tlak na snižování emisí a s tím související masivní podpora elektromobility. Kromě ekologičnosti mají elektrická vozidla řadu dalších výhod, jako například malé provozní náklady, jednodušší údržbu, nižší hlučnost a podobně. V současné době je ovšem stále trápí problémy s dojezdem a nedostatečnou sítí dobíjecích stanic. V městském prostředí tento problém do velké míry odpadá, a naopak ekologické hledisko je zde nejpalčivější. Navíc vzhledem k hustotě městského provozu roste poptávka po jednostopých vozidlech. Řešením je proto elektrický motocykl pro městské prostředí, který tyto problémy efektivně řeší. Proto se práce zabývá návrhem elektrického motocyklu do městského prostředí ve spolupráci s firmou MSR Engines, na technickém základu poskytnutým touto firmou.

The pressure to reduce emissions and the related massive support for electromobility is growing in the world. In addition to environmental friendliness, electric vehicles have several other benefits, such as low operating costs, easier maintenance, lower noise etc. However, they are still bothered by problems with range and an insufficient network of charging stations. In an urban environment, this problem largely disappears, and on the contrary, the ecological aspect is the most pressing here. In addition, due to the density of urban traffic, the demand for single-track vehicles is growing. The solution is an electric motorcycle for the urban environment, which effectively solves these problems. Therefore, the work deals with the design of an electric motorcycle for the urban environment in cooperation with the company MSR Engines, on a technical basis provided by this company.
Design of an Electric Motorcycle
Keywords: design; silniční motocykl; městská mobilita; elektrický pohon; design; road motorcycle; urban mobility; electric drive